Dye Indicator Absorbance Spectra and Complex Ions Formation in Solution - Farasram, P.L.; Farasram, Rakesh; Desai, C.M. (Asian Journal of Chemistry, 2010)
The absorbance of a series of mixed dye, lead nitrate and alkali nitrates solutions, dye concentration and one salt concentration constant and increasing the concentration of the other salt, has been measured. The absorbance at λmax against the other salt concentration shows peaks corresponding to complex ion formations between the salts; this can be explained on the basis of Frank-Condon principle.